Artistic Research in Music: Discipline and Resistance - Impett, Jonathan (Leuven Leuven University Press, 2017)
The Orpheus Institute celebrates 20 years of artistic research in music. Artistic research in music is now at a generational stage of development. How should it deal with its own maturing? From a kaleidoscope of individual pursuits, ethos and methodologies have emerged to encompass more distributed approaches. This transformation has taken place in parallel with changes in the dynamics and structures of culture, its institutions and constituencies. Artistic research maintains a productive dialectic between its potential status as discipline or as practice. It has developed topoi, tropes and its own canon of cases, texts and figures. How does it negotiate relationships with institutions, disciplines and bodies of theory while retaining the critical perspective of the artist? Twenty years ago the Orpheus Institute was founded in Ghent to pursue research through the practice of musicians and thus the Orpheus Institute is of the same generation as the field it was established to explore. This festive volume in honour of 20 years of the Orpheus Institute reviews the initial trajectory and looks ahead to the institute's new position.
Tom Beghin (Orpheus Institute, Ghent), Paulo de Assis (Orpheus Institute, Ghent), Leonella Grasso Caprioli (Conservatorio di Vicenza), Jonathan Impett (Orpheus Institute, Ghent), Esa Kirkkopelto (University of the Arts, Helsinki), Kari Kurkela (University of the Arts, Helsinki), Susan Melrose (Middlesex University, London), Stefan Östersjö (Orpheus Institute, Ghent), Gertrud Sandqvist (Malmö Art Academy), Huib Schippers, Vanessa Tomlinson, Paul Draper (Queensland Conservatorium Research Centre, Griffith University), Luk Vaes (Orpheus Institute, Ghent), Janneke Wesseling / Kitty Zijlmans (Leiden University)
Keywords: Artistic research